Analysis and differences in the basic motor and situational motor abilities between female handball players in the BIH first federal league and the first league of the Republika Srpska - Pavlovic, S.; Talovic, M.; Kazazovic, E.; Lakot, E. (SportLogia, 2013)
The aim of this study was to confirm the difference in basic motor and situational motor abilities of female handball players. Studies were conducted on 77 adult female handball players playing in the BiH First Federal League and the First League of the Republika Srpska. For basic-motor abilities, 18 variables were used which covered factors for estimating segmental speed, flexibility, coordination, power, repetitive power and balance. Situational motor capabilities were tested using five hypothetical latent factors which are responsible for situational efficiency in handball: speed of ball handling, precision, throwing strength, speed without the ball, and ball handling. Discriminative analysis of quantitative differences showed that statistically significant differences exist between the capabilities of players from the BiH First Federal League and the First League of the Republika Srpska. Our results can aid in better understanding, tracking, analyzing and perfecting conditioning and tactical preparation for female handball players at various levels of competition, all in the aim of achieving better quality of competition for senior handball players in BIH..